Asbab al-Nuzul in Surah Al-Baqarah (2): Mulla Huwaisy Perspective of Critical Matn and Sanad - Romdoni, Muhammad Panji (Jurnal Iman dan Spiritualitas, 2023)
It is only possible to interpret the Qur'an by understanding the story of the verses and asbab al-nuzul. Asbab al-nuzul can be accepted if the history is valid. This validity is not just the sanad (narrative series) but also the matn (content). According to Mulla Huways, a scholar from Iraq, in practice, sometimes events are matched to become the asbab al-nuzul of a verse. This research aims to attempt to analyze the concept of asbab al-nuzul according to Mulla Huways, analyzing the criticism of asbab al-nuzul in the interpretation of Bayan al-Ma'ani in surah al-baqarah. This research method uses a qualitative approach with critical analytical reasoning. This research found that: Mulla Huways is of the opinion that asbab al-nuzul in surah al-baqarah is an event or question in the Islamic community where the verse of the Qur'an was revealed as an answer to the event or question. Asbab al-nuzul must match the event and context and category of surah. Using the wrong history of asbab al-nuzul will change the understanding of a verse. Mistakes in the use of asbab al-nuzul are dominated by Makkiyyah surahs. This is due to the narrators' lack of understanding of the history of the revelation of the Koran. By using the nuzuli interpretation method, the errors above can be overcome so that the asbab al-nuzul obtained is valid.